OPTIMATION OF 48 kHz ULTRASONIC WAVE DOSE FOR THE INACTIVATION OF Salmonella typhi - Lestari, Dwi May; Prijo, Tri Anggono; Astuti, Suryani Dyah (Institute of Topical Disease Universitas Airlangga, 2015)
This study was aimed to determine the effect of ultrasonic dose exposure which could decrease the viability of Salmonella typhi by using the variation of exposure time (15, 20, 25, and 30 minutes) and volume of bacterial suspension (2, 4, 6, and 8 ml) at constant power. The sample used was Salmonella typhi. Ultrasonic wave transmitter was a piezoelectric tweeter with 0,191 watts of power and 48 kHz frequency generated by the signal generator. Piezoelectric tweeter was a kind of transducer which converted electrical energy into ultrasonic energy. This research was an experimental laboratory with a completely randomized design. The decrease of bacterial percentage was calculated by using TPC (Total Plate Count). Data were analyzed by using One Way Anova. The results showed that the variation of exposure time and volume of bacterial suspension gave significant effect on the percentage of Salmonella typhi kill. The most optimal of ultrasonic dose exposure to kill Salmonella typhi was 281.87 J/ml with 100% bacterial kill.